THE STATE'S CONTINUING INEFFICIENCY IN BRAZILIAN PRISON LAND WHICH EXTERMINES RIGHTS AND HUMANS BEINGS - Virgulino Ribeiro Nascimento e Gama, Giliarde Benavinuto Albuquerque Cavalcante [UNESP]; Silva Berezowski, Maria Leonice da; Reboucas Porto Junior, Francisco Gilson (Fundacao Univ Tocantins, 2020)
There is a manifest and current instability of the substructures of the Democratic Rule of Law in Brazil, which affects political and social sectors, reflecting the pandemic of 2020 (Sors-CoV-2), This situation does not exempt prisons, which are already delicate and alarming in terms of fundamental rights. In view of this, the objective was to analyze the current reality of prisons in scourges possibly hardened by Sors-Cov-2, in order to reflect the 32 years of the Brazilian Constitution of 1988. Therefore, a bibliographic and documentar study was carried out, qualitatively, to explore the prisons, confirming or refuting the aggravation of the researched locus. It was confirmed that the historical scourges of prisons are worrying as the pandemic advances, which shows the considerable and expressive unpreparedness of prison administrations. Furthermore, the continued inefficiency of prison policies and the ineffectiveness of legal nroms ore confirmed.
Keywords: Pandemic; Prisons; Criminal Law; Human dignity